Pengaruh kepemimpinan transformasional, kepuasan kerja, dan pelatihan terhadap employee engagement melalui kinerja pegawai di Mayapada Hospital - Mattajang, Rio; Nurwulandari, Andini; Yoshua, Yoshua (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Human resources are the most important basic capital in every organization. Without human resources, it is certain that the wheels of the organization will not move. The importance of human resources is not something that has become a new awareness of humans. The purpose of this study was to analyze the effect of Transformational Leadership, Job Satisfaction, Training on Employee Performance and Employee Engagement. The type of research carried out in this study is causal associative research with quantitative techniques. The research sample as many as 168 employees were selected by accidental sampling method. Data collection using questionnaires and Structural Equation Modeling (SEM) was used as an analytical technique. The results of the study prove that the variables of transformational leadership, job satisfaction, training have a positive and significant effect on employee performance and employee engagement. The results of the study have implications for Transformational leadership, Job Satisfaction, Training, which need to be improved in order to improve employee performance and Employee Engagement..